Laser-Engineered Multifunctional Graphene–Glass Electronics; Advanced Materials; Vol. 34, iss. 43 - Rodriguez (Rodriges) Contreras R. D. Raul David; Fatkullin M. I. Maksim Ilgizovich; Garcia Balza A. S. Aura Samid; Petrov I. S. Iljya Sergeevich; Averkiev A. A. Andrey Alekseevich; Lipovka A. A. Anna Anatolyevna; Liliang Lu; Shchadenko S. V. Sergey Vladimirovich; Wang R. Ranran; Jing Sun; Qiu Li; Xin Jia; et al. (2022, 2022)
Title screen